Voices of EFL Teachers as Assessors: Their Opinions and Needs Regarding Language Assessment - Elçin Ölmezer-Öztürk; Belgin Aydın (Anı Publishing, 2019)
Employing a qualitative research design, this study aims to investigate the opinions of EFL teachers regarding their language assessment knowledge and identify their general and skill-based needs in this domain. The participants included 11 EFL teachers who were determined through purposeful sampling and working at different universities in Turkish higher education setting. The data collection process included the participants' responses to seven open-ended questions that focused on their evaluations regarding the findings of a larger study investigating the language assessment knowledge of EFL teachers in Turkey and asked their needs in language testing and assessment. The data were analysed based on the qualitative content analysis by code-labelling and identifying the emerging themes. The findings indicated the insufficiency of trainings in both pre-service and in-service teacher education as the major reason of the low level in language assessment knowledge of EFL teachers. The teachers preferred hands-on trainings given by testing practitioners, and designed to improve them in assessing each skill separately. In the light of these findings, the study offers several suggestions for pre-service and in-service teacher education programs on language testing and assessment.